Effect of Al2O3 on the Tensile and Impact Strength of Flax/Unsaturated Polyester Composite with Emphasis on Automobile Body Applications - Gebre Fenta Aynalem; Belete Sirahbizu (Advances in Materials Science and Engineering)
This study has endeavored to develop an Al2O3-filled natural fiber reinforced polymer composite which is intended to substitute the most widely used synthetic E-glass fiber material. To attain the desired objective of the work, 0, 5, 10, and 15 wt% Al2O3-filled chopped flax/unsaturated polyester resin composite have been developed by the conventional hand-lay-up method followed by a compression molding process. Consequently, characterization and mechanical property tests are conducted based on the ASTM standard. The results revealed that both tensile and impact strength properties of the base chopped flax/unsaturated polyester resin composite are all affected due to the inclusion and variation of the content of Al2O3 in 15 and 25 wt% fiber loading cases. It has been noticed that a 39.06% increase in the ultimate tensile strength of the composite in 25/UPR-5 composition has been gained. The effect of Al2O3 on the impact strength of the base composite has also been analyzed and a 45% increase has been observed in 15/UPR-10 composition. The findings also witnessed that the newly developed composite can be applied to make automotive parts such as mud guard and engine undercover.